SOME BASIC PRINCIPLES IN DESIGNING MATERIALS FOR STUDENTS OF ENGLISH FOR SPECIFIC PURPOSE - Sufiyandi, Muhammad Fadhli (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2020)
Abstract English for Specific Purpose (ESP) has grown up quickly in the area of English Language Teaching (ELT). It is separated from English language teaching in general since the needs for English in a defined context becomes essentially significant. Thus, the central focus of ESP is subjective to the students’ needs. The course is preliminary intended to address what students expect to have and to do in learning activities. One of the important elements in ESP course is material design. In this paper, the discussion is related to some basic principles in designing ESP materials; they are stimulating, sequenced, authentic, and supplemented.